Digital revolution and place of printed books - Maciej Zweiffel (International Journal of Business and Social Science Research, 2021)
“Digital-first” seems to be a crucial idea of our time. From the practical, economic, and even ecological point of view printed books are not the best solution. But still, this practice exists. This survey aims to answer, why in the digital environment occurs the textual niche. Is it a kind of relic or something which is deeply connected with human reading comprehension and the quality of text experience? To solve this problem will be used case study and cognitive methods. The crucial question for the presented paper is whether printed (codex) books and their reading means a form of distributing texts which will be progressively declining under pressure in the digital revolution (Q1). To answer this question, it is necessary to describe the current situation of traditional printing and also raise the question of printed documents especially printed and codex books have any features which cannot be replaced by online publishing (Q2). In the second question, one should take into account the cultural and subjective context of reading or possessing printed books.